(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article synthesizes key concepts regarding the formation and development of the terminology system in the field of information technology. This article serves as a comprehensive resource for specialists, students, and individuals engaged in the information technology sector, providing insights into enhancing their understanding of the terminology system in the field of information technology.